The effects of angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers in critically ill patients with acute kidney injury: An observational study using the MIMIC database - Xu Zhu; Jing Xue; Zheng Liu; Wenjie Dai; Jingsha Xiang; Hui Xu; Qiaoling Zhou; Quan Zhou; Xinran Wei; Wenhang Chen (Frontiers Media S.A., 2022)
Background: The safety of prescribing angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) during acute kidney injury (AKI) remains unclear. We aimed to investigate the associations of ACEI/ARB therapy in AKI with the risk of mortality, acute kidney disease (AKD), and hyperkalemia.Methods: We conducted a retrospective monocentric study, which included patients in Massachusetts between 2008 and 2019 from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Propensity score matching was performed for the endpoint analysis. The association between ACEI/ARB therapy and mortality was assessed using Cox proportional hazards regression models. Logistic regression was used to assess the risk of AKD and hyperkalemia.Results: Among the 19,074 individuals with AKI admitted to the intensive care unit (ICU), 3,244 (17.0%) received ACEI/ARBs, while 15,830 (83.0%) did not. In the propensity score-matched sample of 6,358 individuals, we found a decreased risk of mortality in those who received ACEI/ARBs compared to those who did not (hazard ratio [HR] for ICU mortality: 0.34, 95% confidence interval [CI]: 0.27-0.42); HR for in-hospital mortality: 0.47, 95% CI: 0.39-0.56; HR for 30-day mortality: 0.47, 95% CI: 0.40-0.56; HR for 180-day mortality: 0.53, 95% CI: 0.45-0.62). However, the use of ACEI/ARBs was associated with a higher risk of AKD (risk ratio [RR]: 1.81; 95% CI: 1.55-2.12). There was no significant association between ACEI/ARBs and an increased risk of hyperkalemia (RR: 1.21; 95% CI: 0.96-1.51).Conclusions: ACEI/ARB treatment during an episode of AKI may decrease all-cause mortality, but increases the risk of AKD. Future randomized controlled trials are warranted to validate these findings.